Self-Hypnosis Control of Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
In a prospective study at the Minneapolis Children's Medical Center 28 children with classic migraine were treated with propranolol (3 mg/kg/d) or placebo for 3 months, using a cross over design, followed by an equal period of self-hypnosis.